Analysis of the Layer Farm Business on BUMDes “Mandiri” and Breeder Partners in Babakan Bogor Village Kabawetan Subdistrict Kepahiang District - A. Martini; N. N. Arianti (Universitas Bengkulu, 2021)
This study aims to analyze the income of the BUMDes “Mandiri” layer chicken farm and partner farms, as well as the size of the income earned by BUMDes “Mandiri” and breeder partners from the profit-sharing system carried out together. The research respondents were the BUMDes “Mandiri” farm manager and two breeder partners. Operating income is calculated by finding the difference between business revenues and total business costs incurred. The share received by BUMDes “Mandiri” and partner farmers from partner farm income is determined based on the percentage agreed in the partnership agreement, namely 51% for BUMDes “Mandiri” and 49% for breeder partners. The results showed that the income of the BUMDes “Mandiri” livestock business in one month was Rp. 3,668,890.00 or Rp. 3,668.89/head, while the partner's husbandry business income was Rp. 6,404,505.00 or Rp. 12,809.00/head. The portion of the partner's husbandry business income that belongs to BUMDes “Mandiri” is Rp. 3,266,295.00/month and that which belongs to breeder partners is Rp. 3,138,210.00/month.